Skrining Mamografi dan Mortalitas Kanker Payudara - Catharina Endah Wulandari (PT Kalbe Farma Tbk., 2024)
Breast cancer is the most common cancer in Indonesia and one of the biggest contributor to cancer mortality. About 70% breast cancers are detected at an advanced stage which makes the mortality rate even higher. Several measures have been taken to detect breast cancer early, including mammography screening. Mammography is X-ray imaging used to detect abnormalities in breast cancer. The American College of Radiology recommends breast cancer screening for at-risk women starting at age 40. However, whether mammography screening can reduce breast cancer mortality is still debatable.